Current challenges in porcine medicine: gut health, aspects of neonatal diarrhea, and antibiotic resistance - Tsekouras, N; Athanasiou, LV; Gougoulis, D; Christodoulopoulos, G; Billinis, C; Papatsiros, VG (Journal of the Hellenic Veterinary Medical Society, 2025)
This review explores the critical issues of gut health, neonatal diarrhea, and antibiotic resistance in swine production, underscoring the necessity for integrated management strategies. Maintaining gut health is essential for optimal pig productivity and disease resistance, with disturbances leading to substantial economic losses, particularly from neonatal diarrhea—a major cause of piglet mortality. This condition is influenced by a combination of pathogens, environmental factors, and stressors, demonstrating the need for effective prevention and control measures. Additionally, the review highlights the escalating threat of antibiotic resistance (AMR) in swine farming. Although antibiotics have been instrumental in promoting animal health, their overuse has resulted in the emergence of resistant bacteria, which pose significant challenges to both animal and human health. Notably, strains such as Extended-spectrum beta-lactamase (ESBL)-producing Escherichia coli (E. coli) exacerbate disease management complexities and can be transmitted to humans via the food chain. To combat AMR, the review advocates for stricter antibiotic usage regulations, enhanced farm management practices, and the adoption of the One Health approach, which emphasizes the interdependence of human, animal, and environmental health.